Ecological costs of discrimination: racism, red cedar and resilience in farm bill conservation policy in Oklahoma. Issue 4 (21st August 2020) - Fagundes, Colton; Picciano, Lorette; Tillman, Willard; Mleczko, Jennifer; Schwier, Stephanie; Graddy-Lovelace, Garrett; Hall, Felicia; Watson, Tracy
Abstract: This article makes the case that the legacy of institutional racism by the United States Department of Agriculture (USDA) is connected to the encroachment of the invasive species Juniperus virginiana (eastern red cedar) on farming land. Red cedar's encroachment impacts Black farmers disproportionately in Oklahoma, even as it undermines broader USDA conservation goals and ability to adapt to climate change. As such, this case study illustrates the shortcomings of Farm Bill Conservation Title programs to address ecological issues across the landscape—shortcomings that hinder farmers' ability to carry out long-term adaptation and mitigate risks. Conversely, we show how the work of Oklahoma Black Historical Research Project, Inc. and the Rural Coalition has been vital allies in Black farmers inter-related struggles against racial injustice and red cedar. Thus, we argue community-based organizations have a pivotal, but under-supported, role to play in the shaping and application of farm bill programs and funds.